Development and validation of a novel fibre-optic respiratory rate sensor (FiRRS) integrated in oxygen delivery devices. (14th January 2021) - Sinha, R; Hernandez, Francisco U; He, C; Korposh, S; Correia, R; Norris, A M; Liu, C; Hayes-Gill, B R; Morgan, S P
Abstract: Respiratory rate (RR) monitoring provides crucial information on the overall health condition of patients and a reliable, low cost RR monitor for normal hospital inpatient or home use would be of significant benefit. The proposed system measures light reflection from a Fibre Bragg Grating (FBG) located near, and the total reflection spectrum from a humidity sensing film deposited at, the tip of an optical fibre. Every breath causes a shift in the wavelength reflected from the FBG and intensity change in the overall reflection spectrum. The accuracy of different techniques is investigated in a two-part study with 15 healthy volunteers. In part 1, the participants' respiration rate followed a handheld mobile application at 5, 12 and 30 breaths per minute with simultaneous measurement using the optical fibre system, thoracic impedance pneumography (TIP) and capnometry device (where possible). Two types of medical face masks and a nasal cannula with oxygen delivery rates were investigated. In part 2, participants wore an anaesthetic face mask and breathed at normal and low tidal volumes to evaluate whether low tidal volumes could be detected. The most accurate measurement of RR was through monitoring the Bragg wavelength shift (mean accuracy = 88.1%), followed by the intensity change at the Bragg wavelength (mean accuracy = 78.9%), capnometry (mean accuracy = 77.8%), area under the overall spectrum (mean accuracy = 65.4%) and TIP (mean accuracy = 43.1%). The Fibre-optic Respiratory Rate Sensor system (FiRRS ) can differentiate between normal and low tidal volumes ( p -value < 0.05) and demonstrated higher accuracy than capnometry measurement of end-tidal carbon dioxide in exhaled air. These latter two monitors measured RR more accurately than TIP. A comparable accuracy in the measurement of RR was obtained when the FiRRS was implemented in nasal cannula and face masks.